COMPARISON ANALYSIS OF LINEAR SCHEDULING METHOD (LSM) WITH PRECEDENCE DIAGRAMMING METHOD (PDM) ON DP MALL EXPANSION CONSTRUCTION PROJECT - M. Faizal A A; Anthonius Baraa; Galang Satrio; Agung Budiwirawan (Jurnal Teknik Sipil dan Perencanaan, 2024)
The objective of this study is to analyze the comparison between the Linear Scheduling Method (LSM) and the Precedence Diagramming Method (PDM) in the DP Mall Expansion Project. The main focus of the research is to compare time efficiency, labor cost, and productivity in supporting construction with repetitive tasks. Project scheduling plays a crucial role in construction project development. In the construction industry, more focused scheduling is required for specific types of projects. This study uses a quantitative approach, specifically descriptive-comparative, to compare and analyze project scheduling using the Linear Scheduling Method (LSM) and the Precedence Diagramming Method (PDM). Scheduling analysis and preparation were carried out using Microsoft Excel and Microsoft Project. The scheduling was conducted under two scenarios: normal and accelerated. The analysis focused on architectural works, particularly regarding differences in project duration, labor wage costs, and the effectiveness of scheduling methods for repetitive work. The results show a significant difference between the two scenarios (normal and accelerated) in the Linear Scheduling Method (LSM). However, the accelerated scenario using both LSM and PDM produced the same total duration, number of workers, and labor wages due to the logical dependency relationships in PDM being applicable to LSM. LSM scheduling is more effective for repetitive work, while PDM is less effective for such projects.  This research provides practical contributions for project managers in selecting the appropriate scheduling method according to the specific characteristics of a project. The results indicate that the Linear Scheduling Method (LSM) can be integrated into projects with repetitive tasks to achieve operational sustainability. This study presents a comprehensive analysis of the efficiency of scheduling methods in repetitive construction projects, contributing to project success in terms of time and cost.